1983
DOI: 10.1007/bf00154713
|View full text |Cite
|
Sign up to set email alerts
|

Acyclovir treatment in stromal herpetic keratitis

Abstract: Thirty-five patients with long-standing deep stromal herpes simplex keratitis were treated with 3% acyclovir ointment and corticosteroids. All patients were cured in 2 to 4 weeks, independent of both the duration of the keratitis before acyclovir therapy and the previous antiviral medication. Corticosteroids in tapering dosages had to be continued for many months after healing to prevent recurrence of stromal corneal oedema; recurrences could not be prevented by acyclovir therapy. No serious side-effects of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This is longer than previously reported in a study where all patients with deep stromal keratitis treated with acylovir ointment and 2 5% prednisolone showed resolution of symptoms in one week. 9 However, in the latter study patients were entered if they showed signs of stromal infiltration and were excluded if they had oedema of the disciform type. In addition the concentration of prednisolone used was 50 times greater than that used in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This is longer than previously reported in a study where all patients with deep stromal keratitis treated with acylovir ointment and 2 5% prednisolone showed resolution of symptoms in one week. 9 However, in the latter study patients were entered if they showed signs of stromal infiltration and were excluded if they had oedema of the disciform type. In addition the concentration of prednisolone used was 50 times greater than that used in the present study.…”
Section: Discussionmentioning
confidence: 99%